Developments and innovation in carbon dioxide (CO2) capture and storage technology - Maroto-Valer, M. Mercedes (Woodhead Publishing, 2010)
Annotation Carbon dioxide (CO2) capture and storage is the one advanced technology that conventional power generation cannot do without. CCS technology reduces the carbon footprint of power plants by capturing, and storing the CO2 emissions from burning fossil-fuels and biomass. Capture technology ranges from post- and pre-combustion capture to combustion-based capture. Storage options range from geological sequestration in deep saline aquifers and utilisation of CO2 for enhanced oil and gas recovery, to mineral carbonation and biofixation of CO2. This volume critically reviews carbon capture processes and technology applicable to the conventional power generation sector as well as other high carbon footprint industries.
Keywords: Carbon dioxide mitigation.; Carbon dioxide -- Storage.; Carbon sequestration.; elektronické knihy; electronic books